Stabilization of lateritic soil from Agbara Nigeria with ceramic waste dust. Issue 1 (1st January 2019) - Onakunle, Olumuyiwa; Omole, David O.; Ogbiye, Adebanji S.
Abstract: Geotechnical properties of lateritic soil stabilized with ceramic waste dust (CWD) additive was examined. Specific tests conducted on the modified soil samples include grain-size distribution, Atterberg Limits, Proctor Compaction tests, and California Bearing Ratio tests. Lateritic soil obtained from Agbara, South-West Nigeria and pulverized ceramic materials gathered from construction site rubbles were used for the experiment. The Lateritic soil samples were mixed with ceramic dust from 0 to 30% at an incremental rate of 5%. From the analyses of test results, it was found that Liquid Limit, Plastic Limit, Plasticity Index, and Optimum Moisture Content decreased consistently with the incremental addition of ceramic dust up to 30%, whereas, Maximum Dry Density and California Bearing Ratio (Soaked and Un-soaked) increased with CWD additive. Liquid Limit decreased from 59.62% (unmixed laterite) to 35.61% (30% CWD addition). The Plastic Limit decreased linearly from 40.11% (unmixed laterite) to 23.31% (when mixed with 30% CWD). The percentages for both unsoaked and soaked California Bearing Ratio increased from 6.82% to 21.97% and 4.55% to 14.39% respectively for 5% incremental addition of CWD up to 30%. The study concluded that the use of CWD in the stabilization of lateritic soil is recommended for economic, durability, and environmental advantages.